EFEKTIVITAS PEMANFAATAN INSTAGRAM @KOMINFOBOGOR SEBAGAI MEDIA INFORMASI UNTUK PUBLIK - Syarifudin, Rajwa Shaliha Permata; Dharmawan, Leonard (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2025)
This study aims to observe the effectiveness of Instagram as a social media platform used by the Diskominfo Bogor for delivering information to the public. The study employs a qualitative descriptive design with a case study approach on the official Instagram account @kominfobogor. The results indicate that Instagram is fairly effective in reaching the community, especially the productive age group, by delivering information quickly, visually, and understandably. Features such as feed, reels, and stories facilitate the presentation of information. Instagram also allows two-way interaction through comments and direct messages, although public participation remains limited. Overall, the use of Instagram by Diskominfo Bogor is quite effective as a medium of public communication but still requires development to make communication more interactive and adaptive to the needs of the community.